Interpersonal Character Development of the Main Characters in Sally Rooney’s Normal People Novel (2018) - Dwi Putri Apriliany; Dadan Rusmana; Udayani Permanaludin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the interpersonal character development of Marianne and Connell in Sally Rooney’s novel Normal People (2018). The objective is to analyze how their relationship acts as a catalyst for their transformation into round characters and to identify the characterization techniques used to portray this growth. The analysis focuses on three dimensions of personality complexity which are self-perception, relational power/social position, and emotional vulnerability. This study uses a qualitative descriptive method with an objective literary criticism approach and applies the theory of character and characterization by E. M. Forster as the main theory, along with characterization theories by Robert Stanton and Hawthorn. The results show that Marianne and Connell experience significant transformations due to the interpersonal relationships they go through. Marianne develops from a socially isolated individual with low self-esteem into someone who gains social acceptance and has a healthier understanding of emotional dependence. Meanwhile, Connell develops from an individual who has social stability but is internally vulnerable into someone who becomes aware of his emotional needs and is able to express his vulnerability to Marianne. This development confirms that both characters are complex and dynamic round characters. In addition, Rooney mainly uses indirect characterization techniques through narration, dialogue, and the characters’ thoughts, which allow readers to understand the characters’ development processes in depth, while direct characterization is used in a limited way to build the initial image of the characters. Therefore, interpersonal relationships play a key role as the main mechanism in driving character development in this novel.